A human cardiomyocyte screen identifies optimized lipid nanoparticles for in vivo cardiac gene editing - Yehui Sun; Yu-Chung Pien; Yufen Xiao; Wei Tan; Efrain Sanchez-Ortiz; Mateusz Z. Durbacz; Zexiang Chen; John R. McAnally; Yu Zhang; Hui Li; Andreas C. Chai; Francesco Chemello; et al. (Proceedings of the National Academy of Sciences, 2026)
RNA therapeutics offer promising potential for treating heart disease; however, their clinical application has been limited by insufficient cardiac delivery. Here, we developed a screening platform using human induced pluripotent stem cell–derived cardiomyocytes (hiPSC-CMs) to identify human cardiotropic lipid nanoparticles (LNPs). By screening a chemically diverse LNP library, we identified a lead LNP, 18:1 TAP10, with potent human cardiac transfection capability. Using the Ai14 LoxP-Stop-LoxP-tdTomato reporter mouse model, we assessed 18:1 TAP10 LNP delivery of Cre mRNA in vivo via four administration routes (intravenous, intrathoracic, intracoronary, and intramyocardial (IM)) and found that each administration path enabled both the spatial distribution and cellular tropism in the heart to varying degrees. While all routes achieved robust transfection across non-CM populations (up to 40% in endothelial cells), IM injection notably enabled substantial CM transfection (36% at injection site, 13% distally). To demonstrate therapeutic potential, 18:1 TAP10 LNPs were used to deliver adenine base editor (ABE) components to Duchenne muscular dystrophy (DMD) patient-derived hiPSC-CMs, resulting in 80% on-target gene correction and restoration of dystrophin expression. In a humanized DMD mouse model, we observed dystrophin-positive cardiomyocytes in the injected left ventricle following IM administration of LNP-ABE. This work establishes a human cell-based platform for discovering organ-tropic delivery vehicles and highlights LNPs as a potential modality for therapeutic mRNA delivery and gene editing in the heart.